2012
DOI: 10.1021/jo301597h
|View full text |Cite
|
Sign up to set email alerts
|

Imidazolium Hydrogen Carbonates versus Imidazolium Carboxylates as Organic Precatalysts for N-Heterocyclic Carbene Catalyzed Reactions

Abstract: Imidazolium-2-carboxylates (NHC-CO(2) adducts, 3) and (benz)imidazolium hydrogen carbonates ([NHC(H)][HCO(3)], 4) were independently employed as organic precatalysts for various molecular N-heterocyclic carbene (NHC) catalyzed reactions. NHC-CO(2) adducts were obtained by carboxylation in THF of related free NHCs (2), while the synthesis of [NHC(H)][HCO(3)] precursors was directly achieved by anion metathesis of imidazolium halides (1) using potassium hydrogen carbonate (KHCO(3)) in methanolic solution, withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 81 publications
(144 reference statements)
4
68
0
Order By: Relevance
“…Three different organocatalyzed reactions of molecular chemistry were implemented, namely, transesterification, benzoin condensation and cyanosilylation of aldehydes, known as being efficiently catalyzed by both molecular NHCs and ([NHC(H)][HCO 3 ]) salt precursors …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three different organocatalyzed reactions of molecular chemistry were implemented, namely, transesterification, benzoin condensation and cyanosilylation of aldehydes, known as being efficiently catalyzed by both molecular NHCs and ([NHC(H)][HCO 3 ]) salt precursors …”
Section: Resultsmentioning
confidence: 99%
“…In addition, progressive hydrolysis of NHC‐CO 2 adducts, forming imidazol(in)ium hydrogen carbonates, denoted as [NHC(H)][HCO 3 ], has been reported . However, we have shown that these salts can serve as a genuine source of NHCs under very mild conditions, formally by a loss of “H 2 CO 3 ” (H 2 O +CO 2 ) . Synthesis of [NHC(H)][HCO 3 ] precursors can be readily achieved in one pot, by anion exchange from commercial imidazol(in)ium halides ([NHC(H)][X]; X = Br or Cl), in the presence of KHCO 3 in methanol.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, more stable NHC adducts with haloalkanes,17 alcohols,18 silver,19 CO 2 ,20 and H 2 CO 3 21 have been developed to liberate NHCs on demand under base‐free conditions. Among these masked NHCs, zwitterionic (dihydro)imidazolium‐2‐carboxylates ((H 2 )IMes‐CO 2 ) gain much attention owing to their accessibility, good stability, and easy generation of the respective free NHCs 13b. 14b, 20c…”
Section: Methodsmentioning
confidence: 99%
“…Among them hydrogen carbonate and hydroxide are particularly important. As regards 1,3-dialkylimidazolium hydrogen carbonates, it is reported that these ionic liquids are in equilibrium with the corresponding NHC-CO 2 adducts (vide infra), demonstrating the possibility to afford NHCs (see for example: Fèvre et al, 2012; Zhao et al, 2017) by releasing of carbon dioxide due to high temperature effect or, at room temperature, using a solvent favoring the carbene generation (as THF or toluene).…”
Section: Experimental Studiesmentioning
confidence: 99%